Oral health literacy: its impact on oral health outcomes and associated factors in sixth-grade primary school students – a cross-sectional study - Kirana Kamolchaiwanich; Pinpinut Wanichsaithong (BMC Oral Health)
Abstract Background Low oral health literacy (OHL) plays a crucial role in contributing to poor oral health outcomes. However, limited studies have focused on school-age children. This study aims to investigate the association between OHL among sixth-grade primary school students and oral health outcomes, and to identify factors related to inadequate OHL. Methods A cross-sectional study was conducted among 408 Thai sixth-grade primary school students (aged 12 years) in Pathum Thani Province, Thailand. Participants completed the Test of Functional Health Literacy in Dentistry for Primary School Children (P-TOFHLiD) to assess OHL and underwent oral examinations. Oral health behaviors were collected through participant interviews and caregiver questionnaires, while demographic data were obtained from caregiver questionnaires. Chi-square tests, Spearman’s correlation, and logistic regression were used to assess associations between OHL and oral health outcomes, and to identify risk factors for inadequate OHL. Results The mean P-TOFHLiD score was 19.4 (SD = 4.7), with a median of 21 (IQR: 17–23). 59.6% had inadequate OHL (score < 21). Chi-square tests showed that participants with inadequate OHL were more likely to have untreated caries in permanent teeth (p < 0.001), first permanent molars with disease-related pulp exposure (p = 0.001), poorer oral hygiene (p < 0.001), and consumption of cariogenic snacks (p < 0.001), while no associations were found with missing or filled permanent teeth, brushing frequency, fluoridated toothpaste use, or dental service utilization. Logistic regression showed that inadequate OHL increased the odds of having untreated caries in permanent teeth (AOR = 8.30, 95% CI: 4.89–14.11), first permanent molars with disease-related pulp exposure (AOR = 20.63, 95% CI: 4.84–87.91), and poor oral hygiene (AOR = 2.08, 95% CI: 1.20–3.59). Lower Grade Point Average (GPA) (AOR = 0.01, 95% CI: 0.00–0.02) and low family income (< 10,000 Baht) (AOR = 3.56, 95% CI: 1.62–7.82) were associated with increased risk of inadequate OHL. Conclusions Inadequate OHL was linked to adverse oral health outcomes. Lower GPA and low family income were identified as risk factors for inadequate OHL. These findings emphasize the need for targeted interventions to strengthen OHL and improve children’s oral health. Trial registration Not applicable.